Does glycated haemoglobin (HbA1c) correlate with the Ankle-Brachial Index (ABI) among patients with type 2 diabetes in Indonesia? An evaluation study - Azali, Lalu Muhammad Panji; Yudaningsih, Reynanda Fellicia Sri; Saelan, Saelan; Yuliningsih, Endang (Innovation in Health for Society, 2026)
Type 2 Diabetes (T2D) is a chronic metabolic disorder characterized by hyperglycaemia, which can lead to severe microvascular and macrovascular complications over time. These issues typically emerge from suboptimal disease management, particularly poor glycaemic control. Ineffective T2D management not only fails to regulate blood glucose but also accelerates vascular complications such as Peripheral Arterial Disease (PAD), which can be clinically measured through a decline in the Ankle-Brachial Index (ABI). Consequently, monitoring both HbA1c and ABI is essential for tracking diabetes progression. This study analysed the correlation between HbA1c levels and ABI values in T2D patients to support the early detection of vascular complications and improve comprehensive disease management. Employing a quantitative approach with a cross-sectional design, the study evaluated a population of 163 patients at Ibu Fatmawati Soekarno General Hospital, Surakarta. Purposive sampling was applied to select 62 respondents who met the inclusion criteria: willingness to participate, a confirmed T2D diagnosis, and a history of glycated haemoglobin (HbA1c) laboratory testing. Research instruments included a clinical examination sheet, a sphygmomanometer, and a handheld Doppler device. Statistical analysis using Kendall’s tau-b test yielded a p-value of 0.000 (p<0.05). The correlation coefficient of -0.615 indicated a moderately strong negative correlation, demonstrating that higher (poorer) HbA1c levels are significantly associated with lower (worse) ankle-brachial index values. Nurses with expertise in diabetes care must pay close attention to these findings. Innovation is highly imperative to address this issue and effectively prevent diabetic foot ulcer (DFU). Keywords: Ankle Brachial Index, diabetic foot prevention, glycated haemoglobin, nursing care, type 2 diabetes